Community-Based Tourism to Support Sustainable Tourism: Comparative Study in Sesaot (Indonesia) and Ban Na San (Thailand) - Nabila Putri Azahra; Akhmad Saufi; Embun Suryani (Khazanah Sosial, 2025)
This study explores the dynamics of community-based tourism (CBT) as a pathway to sustainable development in two culturally distinct Southeast Asian contexts: Sesaot Village in Lombok Barat, Indonesia, and Ban Na San District in Surat Thani, Thailand. Employing a qualitative case study approach, this research integrates triangulated data from interviews, observations, and document analysis, framed through a source-by-triangulation method. This study adopts content analysis and finds for: (1. Community participation and empowerment); (2. Sustainable governance and institutional synergy); (3. Capacity building and socio-cultural benefits); (4. Local challenges and institutional barriers). The findings reveal that while Sesaot relies heavily on informal leadership, cultural values, and grassroots participation, Ban Na San operates within a more structured and state-supported tourism governance framework. Despite these differences, both communities exhibit strong local identity, willingness to innovate, and a commitment to sustainability. The study concludes that CBT is most effective when it empowers communities through inclusive governance, sustained capacity-building, and locally relevant tourism strategies. These findings contribute to theoretical discussions on grassroots development and offer practical implications for CBT implementation.